Output/input ratios in single and multipurpose cattle - Zerbini, E.; Gebre-Wold, A. (Ethiopian Society of Animal Production, 1995)
This discussion which is based on output/input ratios includes many factors which are likely to be extremely important in relation to the overall utilization of feed by multipurpose cattle. It compares different output/input ratios (biological efficiencies) for draught work, beef production, milk production and milk + draught work functions. Some of the calculations have been done using data from experiments Reporting measured ME intakes, while in others ME intake has been estimated from live weight.